2020
DOI: 10.31234/osf.io/f6c3p
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors influencing recovery in opioid substitution treatment: a systematic review and thematic synthesis

Abstract: Background and Aims Recovery outcomes for opioid substitution treatment are poorer than those for alcohol and other drugs. In order to understand why this is and to synthesise the findings of a large number of qualitative studies, we conducted a systematic review and thematic synthesis to understand facilitators of and barriers to recovery from opioid dependency. Methods Electronic databases (Pubmed, PsychInfo, CINAHL and Embase) were searched. English language studies exploring the views of adult service user… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 57 publications
0
4
0
1
Order By: Relevance
“…By considering findings in relation to the socioecological model, we have shown that treatment journeys within OAT are constrained by complex interactions between the individual and wider contextual factors. Our study therefore builds upon the work of previous researchers who have explored treatment experiences in OAT from an ecological perspective (e.g., [ 39 , 45 , 46 ]) and specifically offers consideration of these factors within the UK treatment system. Adopting a systems perspective is key to developing interventions that take into account contextual factors and the relationships between these [ 90 , 91 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By considering findings in relation to the socioecological model, we have shown that treatment journeys within OAT are constrained by complex interactions between the individual and wider contextual factors. Our study therefore builds upon the work of previous researchers who have explored treatment experiences in OAT from an ecological perspective (e.g., [ 39 , 45 , 46 ]) and specifically offers consideration of these factors within the UK treatment system. Adopting a systems perspective is key to developing interventions that take into account contextual factors and the relationships between these [ 90 , 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…Socioecological approaches allow for the exploration of issues across five levels: individual, intrapersonal, organisational, community and policy [ 38 ]. Such models are increasingly used to study public health issues, including opioid use and dependency (e.g., [ 39 , 40 , 41 , 42 , 43 , 44 ]). However, only a small number of studies have adopted this approach to specifically explore experiences of OAT [ 39 , 45 , 46 ], and, to our knowledge, no studies have been conducted in a UK treatment context.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach is more likely to sustain prevention efforts over time and achieve population-level impact. Since its inception, the SEM has been utilized, modi ed, and applied within various public health promotion contexts, including contextualizing the opioid crisis [13][14][15][16][17][18][19][20][21]. Its use is a practical approach for assessing the multi-faceted barriers and facilitators of Naloxone use and informs the development of evidence-based community interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Detta beror dels på den maktobalans som förekommer generellt mellan brukare och (företrädare för) välfärdsorganisationer och som kan härledas till olika positioner och kunskapsnivåer (Börjesson & Rehn, 2009;Nordgren, 2003), dels på att den asymmetriska maktrelationen förstärks när det som i LARO handlar om en livsnödvändig medicin som personalen styr över och patienterna behöver Järvinen & Miller, 2010;. Stigmatiserande samhällsattityder kring LARO och droganvändning generellt kan dessutom ha betydelse även i det här sammanhanget (Carlisle et al, 2020;Hatzenbuehler et al, 2013;Matthews et al, 2017).…”
unclassified